Giving a Voice to the Little Ones: The Bioarchaeology of Children in the Baltics - Morrone, Alessandra (Archaeologia Lituana, 2020)
The skeletal remains of non-adults provide endless insights into numerous aspects of their personal, family and social lives. Although they were considered to be marginal members of society, children can potentially shed light on factors influencing the overall health and survival of their communities, sensitively conveying the ability of a population to adapt to its environment and cope with moments of crisis. In the last decade, worldwide interest in the archaeology of children has grown, and has driven the bioarchaeological investigation of their skeletal remains. However, the bioarchaeological study of non-adults has received surprisingly little interest in the Baltic states. This review presents the past and current state of the art with specific focus on the Baltic area from prehistory to historic times, outlining new research fields and the benefits of studying non-adult skeletal remains, and proposing specific possible directions for future work on this topic. The paper is aimed at giving a louder voice to the youngest actors of ancient communities, and perhaps offers a starting point for developing a definitive bioarchaeology of children in the Baltics.
Keywords: Bioarchaeology of children; Baltic bioarchaeology; Estonia; Latvia; Lithuania; Livonia